2006
DOI: 10.1039/b610317k
|View full text |Cite
|
Sign up to set email alerts
|

Control and prediction of packing motifs: a rare occurrence of carbamazepine in a catemeric configuration

Abstract: A predicted orthorhombic crystal structure of carbamazepine is isostructural with an experimentally determined dihydrocarbamazepine crystal structure, providing a rationale for synthesising a novel 1 : 1 solid solution that has carbamazepine in a rare catemeric configuration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 12 publications
(11 reference statements)
0
55
0
Order By: Relevance
“…Cruz-Cabeza et al (2007b) suggested that there was a kinetic disadvantage for carbamazepine to form strained hydrogen-bonding chains. Crystallizing carbamazepine with the closely related molecule dihydrocarbamazepine (XVIIb) led to a solid solution (Florence, Leech et al, 2006), which was isostructural with the catemeric dihydrocarbamazepine form II, showing carbamazepine could form the required hydrogen bonds. Finally, subliming carbamazepine onto a crystal of dihydrocarbamazepine form II led to the formation of the first crystals of carbamazepine form V, the targeted isostructural form (Arlin et al, 2011).…”
Section: Because the Right Crystallization Experiments Has Not Yet Beementioning
confidence: 99%
“…Cruz-Cabeza et al (2007b) suggested that there was a kinetic disadvantage for carbamazepine to form strained hydrogen-bonding chains. Crystallizing carbamazepine with the closely related molecule dihydrocarbamazepine (XVIIb) led to a solid solution (Florence, Leech et al, 2006), which was isostructural with the catemeric dihydrocarbamazepine form II, showing carbamazepine could form the required hydrogen bonds. Finally, subliming carbamazepine onto a crystal of dihydrocarbamazepine form II led to the formation of the first crystals of carbamazepine form V, the targeted isostructural form (Arlin et al, 2011).…”
Section: Because the Right Crystallization Experiments Has Not Yet Beementioning
confidence: 99%
“…The anti-oriented N-H group is not utilized in the formation of the supramolecular complex thereby breaking Etter's first rule of hydrogen bonding which states 'all good proton donors and acceptors are used in hydrogen bonding' (Etter, 1990). More recently the preparation and structure determination of the computationally predicted Florence, Leech et al, 2006) catemeric Form V was achieved by using a seed crystal of the catemeric orthorhombic Form II of DHCBZ (Harrison et al, 2006) to template growth of a crystal of Form V of CBZ from the vapour phase (Arlin et al, 2011). In this example, the anti-oriented N-H group participates in the formation of the catemeric chain leaving the syn-oriented N-H donor uncoordinated.…”
Section: Introductionmentioning
confidence: 99%
“…This difference in molecular structure may explain why it has not been possible to form a 1-1 solid solution of CYH:DHC, whereas a solid solution of CBZ:DHC can be readily obtained via slow evaporation from ethylacetate solution. 20 Despite this difference in molecular structures, the targeted growth of CYH-III on DHC-II occurs highlighting the flexibility of the computationally assisted template induced crystallisation method.…”
mentioning
confidence: 99%